Analgesic efficacy and safety of epidural and paravertebral blocks in thoracotomy surgery - Onur, Tuğba; Demirel, Asiye; Onur, Anıl; Ozgunay, Seyda Efsun; Karaca, Ümran; Engin, Mesut (The European Research Journal, 2023)
Objectives: Epidural anesthesia, once considered a gold standard, has significant complications: hypotension, urinary retention, and catastrophic neurological damage in rare cases. While paravertebral analgesia can provide similar analgesic effectiveness to epidural analgesia, it is associated with fewer side effects. To compare the perioperative and postoperative effects of epidural (ED) and ultrasound-guided paravertebral block (PVB) applications in thoracotomy surgeries. Methods: Fifty-two patients underwent elective thoracotomy; Group 1 (ED, n = 23) and Group 2 (PVB, n = 29) were evaluated. A comparison of hemodynamic parameters and complications preoperatively and postoperatively, postoperative analgesia requirements, visual analog scale (VAS) pain scores within 24 hours at specified times, the amount of analgesic used, the time to mobilize, the time to discharge, and the VAS values measured at three months was made. Results: There was no difference between the study groups regarding demographic and ASA values, most comorbid chronic diseases, obesity, and smoking. The number of attempts, the postoperative 2nd hour VAS score, and the doses of paracetamol and tramadol used was significantly higher in Group 1 than in Group 2 (p = 0.002, p = 0.002, p = 0.012, and p = 0.022, respectively). There was no statistical difference between the groups in terms of postoperative 6, 12, 24 hours, and 3 months VAS scores, first mobilization and discharge, time to remove the thorax tube, intensive care (PACU) need, and perioperative and postoperative complications (p > 0.05). Conclusions: Ultrasound-guided PVB can be considered a safe and effective alternative to ED in thoracotomy surgery.